Study on the Influence of Bearings on Transmission Efficiency of Manual Transmission and Optimization - Wenjian Fan; Xiangkui Kong; Wanxin Mao; Hong Zhang (Jixie chuandong)
Energy saving and emission reduction is an important trend in the development of automotive industry. As the core component of transmission system，transmission needs to be further optimized to improve its transmission efficiency. The bearing of a domestic 5-speed manual transmission is studied. The influence of bearing accuracy，bearing clearance and bearing sealing structure on transmission efficiency under different working conditions is considered. The results show that the improvement of bearing accuracy can improve the transmission efficiency in low gear，but has little effect on the transmission efficiency in high gear； compared with the original bearing clearance （C3 group），both Cm group and C5 group can improve the transmission efficiency，but the working condition improved by Cm group clearance is closer to the real working condition； the friction torque generated by the bearing seal accounts for more than 85% of the total friction torque of the bearing. The optimization scheme of transmission bearing is formulated. Through the vehicle WLTC （World-wide harmonized light duty test cycle） fuel consumption，it is found that the use of Cm group bearing clearance and non-contact sealing structure can reduce the vehicle WLTC fuel consumption by 0.97%.